Trainings to Train Teachers Helping Dental Students Learn Ethics: Feedback of the Participants - Piryani, Rano Mal; Piryani, Suneel (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Short-term trainings for faculty members in ethics at different contexts have been shown positive impact. The objective of this study was to assess the feedback of the participant faculty. MATERIAL AND METHODS: Three short trainings to train teachers helping dental students learn ethics were organized in Jan-Feb 2019 in Universal College of Medical Sciences Bhairahawa Nepal. Twenty-five dental faculty members participated in these training; each training was of four hours. At the end of each training feedback was taken from the participants on semi-structured questionnaire. RESULTS: The rating of participants was notable on scale 1-10 for usefulness (8.84±1.03), content (8.36±1.35), relevance (8.68±0.90), facilitation (8.72± 1.21) and overall 8.92± 0.91. Their confidence level in conducting and facilitating "Think-Pair- Share" interactive session (3.68±0.69) and "Group-Work Discussion" (3.76±0.83) have increased on Likert scale 1-5. Participants rated teaching dental clinical ethics session as extremely important (3.96±0.20) on Likert scale 1-4. The participants also expressed they understand the importance of ethics teaching and practices and gained confidence to teach ethics to students. CONCLUSION: The rating on the training is notable; the perception of participants was positive regarding training and training enhanced their confidence to teach students.